Prevalence of Rheumatoid Arthritis and Spondyloarthritis in Turkey: A Nationwide Study - Dilşad SİNDEL and Savaş GÜRSOY and Sami HİZMETLİ and Ece KAPTANOĞLU and Önder KAYHAN and Mehmet KIRNAP and Siranuş KOKİNO and; n KOZANOĞLU and; KURAN and; l NAS and; l. (Archives of Rheumatology, 2018)
Objectives: This study aims to estimate the prevalence of rheumatoid arthritis (RA) and spondyloarthritis (SpA) in Turkey using the same telephone questionnaire developed for screening RA and SpA in France and used in Serbia and Lithuania. Material and methods: The study was performed in two steps. In step I, the French questionnaire was translated into Turkish and validated through a group of 200 patients (80 males, 120 females; mean age 44.0±13.1 years; range 19 to 75 years) followed up at the rheumatology departments of University Hospitals in Antalya and Ankara. In step II, the validated Turkish questionnaire was administered face-to-face to randomly selected 4,012 subjects (1,670 males, 2,342 females; mean age 41.5±16.8 years; range 16 to 97 years) by trained general practitioners across the country, in 25 prov- inces for case detection. The subjects who were suspected of having RA or SpA in accordance with the questionnaire were invited to the nearest university hospital for rheumatologic examination in order to confirm the diagnosis. Results: In step II, a total of 25 subjects (2 males, 23 females) were diagnosed as RA. The standardized RA prevalence for the general population of Turkey was calculated as 0.56% (95% confidence interval [CI]; 0.33-0.79), 0.10% (95% CI; -0.05-0.25) for males and 0.89% (95% CI; 0.51-1.27) for females. A total of 18 subjects (3 males, 15 females) were diagnosed as SpA. The standardized SpA prevalence for the general population of Turkey was 0.46% (95% CI; 0.25-0.67), 0.17% (95% CI; -0.03-0.37) for males and 0.65% (95% CI; 0.32-0.98) for females. The prevalence of RA was highest in the Northern region (2.00%) and the prevalence of SpA was highest in the Central region (1.49%). Conclusion: The prevalences of RA and SpA in Turkey are close to each other and there are significant inter-regional variations in prevalences of both RA and SpA.